1984
DOI: 10.1111/j.1365-2125.1984.tb05005.x
|View full text |Cite
|
Sign up to set email alerts
|

Clofibrate enhances the affinity of insulin receptors in non‐insulin dependent diabetes mellitus.

Abstract: Glucose-lowering mechanism by clofibrate was studied in non-insulin dependent diabetics managed with dietary therapy alone. Clofibrate 1500 mg was administered for 1 month to 15 patients, and 75 g oral glucose tolerance test and insulin tolerance test were carried out before and after 1 month of the treatment. Fasting plasma glucose values were decreased from 9.34 + 0.53 mmol/l to 7.58 ± 0.33 mmol/l (P < 0.01), and fasting insulin levels were decreased from 13.8 ± 1.7 ,uu/ml to 10.1 + 1.5 5,u/ml (P < 0.05). Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Increased affinity of insulin receptors has been reported (11). We tested 10 subjects before and after either placebo or treatment with clofi- brate.…”
Section: Discussionmentioning
confidence: 99%
“…Increased affinity of insulin receptors has been reported (11). We tested 10 subjects before and after either placebo or treatment with clofi- brate.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PPARα activation in skeletal muscles shifts substrate utilization from glucose to FA, a conclusion supported by loss-of-function experiments (73,83). However, only a few clinical trials report an improvement of glucose homeostasis after fibrate treatment (84)(85)(86)(87). Moreover, the recent Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study did not reveal any effect of fenofibrate on glucose parameters in diabetic patients (88); this suggests that effects on glucose homeostasis may be species specific.…”
Section: Glucose Metabolismmentioning
confidence: 93%
“…Fasting plasma glucose, oral glucose tolerance test results, and immunoreactive insulin in these patients are significantly decreased, which is accompanied by enhanced glucose use and decreased serum TGs and cholesterol [ 371 ]. Furthermore, clofibrate in patients with non-insulin-dependent diabetes decreases fasting plasma glucose and insulin levels, and insulin binding to erythrocytes is enhanced because of increased insulin receptor affinity without a change in receptor number [ 372 ]. Another study showed that clofibrate ameliorates glucose tolerance in this patient population without changing the number of insulin receptors and that this increased insulin sensitivity occurs via an unknown post-receptor mechanism [ 373 ].…”
Section: Insulin Signalingmentioning
confidence: 99%